1998
DOI: 10.1143/ptp.99.489
|View full text |Cite
|
Sign up to set email alerts
|

From Nagaoka's Ferromagnetism to Flat-Band Ferromagnetism and Beyond: An Introduction to Ferromagnetism in the Hubbard Model

Abstract: It is believed that strong ferromagnetic interactions in some solids are generated by subtle interplay between quantum many-body effects and spin-independent Coulomb interactions between electrons. It is a challenging problem to verify this scenario in the Hubbard model, which is an idealized model for strongly interacting electrons in a solid.Nagaoka's ferromagnetism is a well-known rigorous example of ferromagnetism in the Hubbard model. It deals with the limiting situation in which there is one fewer electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
245
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(250 citation statements)
references
References 63 publications
(193 reference statements)
2
245
1
Order By: Relevance
“…We limit our discussions to the most well-studied 2D FBs, and purposely avoid invoking abstract mathematical derivations in this article. With the intuitive pictures provided here, we encourage the readers to work on more specialized literature for the rigorous proof [24][25][26]. Also, we primarily focus on realizing electronic FBs in solid-state materials using the charge degree of freedom.…”
Section: Introduction and Scopementioning
confidence: 99%
“…We limit our discussions to the most well-studied 2D FBs, and purposely avoid invoking abstract mathematical derivations in this article. With the intuitive pictures provided here, we encourage the readers to work on more specialized literature for the rigorous proof [24][25][26]. Also, we primarily focus on realizing electronic FBs in solid-state materials using the charge degree of freedom.…”
Section: Introduction and Scopementioning
confidence: 99%
“…Bands that are nearly flat and/or feature a nontrivial topological invariant, similar to Landau levels producing the quantum Hall effects [2][3][4], have been considered in recent theoretical works [5][6][7][8][9][10][11][12] and can be realized in ultracold gas experiments [13][14][15]. Flat-band ferromagnetism has been studied first by Lieb [16] and, subsequently, by Tasaki and Mielke [17][18][19][20]. More recently it has been shown that the high density of states of flat bands enhances the superconducting critical temperature [21,22].…”
mentioning
confidence: 99%
“…Flat bands, or quasiflat bands, can be realized in bipartite lattices [16] and other models [6][7][8]20,24]. A simple bipartite lattice featuring a strictly flat band is the Lieb lattice [ Fig.…”
mentioning
confidence: 99%
“…[1,[24][25][26]), which is located at the middle of the spectrum. This flat band is one from the total of three bands of the Lieb lattice, consistent with the three atoms unit cell.…”
Section: Introductionmentioning
confidence: 99%